Operational hedging of exchange rate risks - Jan Tscheke (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
Exchange rate exposure of firms diminishes when imported intermediates and exports are denominated in currencies that move together. Appreciations of the domestic currency, raising foreign currency export prices, then also reduce marginal costs, allowing firms to counter the increase in foreign prices. Using firm-level data from seven European countries I estimate a structural model showing how exchange rate pass-through into sales depends on intermediate imports and the co-movement of export and import related exchange rates. I find that operational hedging requires firms to intentionally choose export and import regions with comoving currencies. Analyzing the locational choice of firms confirms that the co-movement of currencies indeed appears to be taken into consideration
urn:nbn:de:bvb:19-epub-30227-5
Keywords: D21; D22; F12; F14; F31; G15; L21; L23; L25; M16; 330; Hedging; Offshoring; Intermediate Imports; Foreign Sourcing; Exporter; Effective Exchange Rates; Pass-Through; Disconnect Puzzle; Exchange Rate Co-Movement